(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A generalised definition of HVG[4] say HVG is considered with the vertex sets [4]. To analyse graph theoretic properties of HVG for any value of it is very much necessary to find the position of each and every point of the vertex set . For this we have derived some fruitful results which help us to find out the position of each and every vertex set and those results also help us to generate any vertex set of period without knowing . Some graph theoretic properties of mHVG is discussed in this paper.